Pré-natal de mulheres residentes no município de Santarém Pará entre 2014 a 2023. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Prenatal care is one of the most important components for the care and monitoring of women's health during the gestational period, becoming essential for the protection and prevention of adverse events. In Brazil, this monitoring is carried out through the Unified Health System (SUS), through Primary Health Care (PHC) teams. The objective of this study was to characterize the profile of women living in the city of Santarém regarding prenatal care, based on epidemiological data available from the period 2014 to 2023. This is an epidemiological study, with a quantitative, descriptive, exploratory approach, using data available for public consultation. Data collection was carried out in the Live Birth Information System, using the following variables: maternal age, marital status, level of education, duration of pregnancy, prenatal consultations, type of birth, type of pregnancy, place of occurrence, sex and color/race. Data were collected on the website and organized into tables for data analysis. It was identified that in the period studied there were 66,207 live births. Of these women who had children, around 99.9% were of childbearing age and were monitored in the city's health care network. Regarding the sociodemographic profile, 69.9% were aged between 15 and 29 years; the majority had a consensual marital status (53%), followed by single mothers (27.6%); they had an education level of 8 to 11 years (67%) and declared themselves mixed race (92.8%). Regarding the characterization of prenatal care and childbirth, it was found that the majority had 7 or more consultations (55.1%); had a baby considered full-term (80.3%), As for the number of conceptuses, single pregnancy prevailed (98.4%), with a prevalence of births of male babies (51.1%), the main route was vaginal birth (65.6%) and the place of births occurred mainly in a hospital environment (93.7%). It is worth highlighting the presence of births occurring at home (6%) and the presence of women who were not accompanied during prenatal care (1.9%), this may be related to the difficulty in accessing PHC and hospitals in the city due to the location of residence. Based on the description of the prenatal profile of women in the city of Santarém, this work preliminarily concludes that most of the recommendations described in public policy regarding care during the gestational period were followed. The results of this study can support discussions about access to health services in urban, rural, quilombola, indigenous and riverside territories and about the implementation of public policies guaranteeing comprehensive assistance that reflects the improvement of maternal and child health indicators.
Keywords: Mulheres; Gestantes; Cuidado Pré-Natal; CNPQ:: CIÊNCIAS DA SAÚDE